The Penguin companion to literature ; U.S.A. - Mottram, Eric; Bradbury, Malcolm, 1932-2000; Franco, Jean (Allen Lane, 1971)
Attempts to provide a broad coverage of the most important names in American writing from the early period of settlement through to the immediate present, including figures of historical as well as directly literary interest. Gives a strong representation to twentieth-century literature.